Teachers' Perspectives on The Impact of The Digital Era on Education - Manurung, Ria; Eva Angelia Krsitina , Marpaung; Intana , Siregar (Journal of Sumatera Sociological Indicators, 2023)
The presence of such widespread technological acceleration is expected to be able to solve various challenges and social problems by utilizing various innovations that were born in the era of the Industrial Revolution 4.0 to improve the quality of human life. Many changes in human convenience are brought about by technology, including economic, social, cultural, industrial, and even educational advancements. Therefore, the purpose of this research is to find out the changes and the impact of teaching methods felt by teachers as they transition from conventional to digital methods. The method used in this research is qualitative analysis, and it uses primary data as the data source. The results of this study indicate that teachers feel a positive impact from utilizing digital media on the learning process for students. The media used are Zoom meetings, e-learning, learning materials from YouTube, and learning materials from various sources on the internet. so that this method is felt to be more efficient, practical, creative, and innovative compared to conventional methods. Therefore, this paper concludes that the impact of digital media has a positive influence on the world of education, especially for teachers. So by continuing to utilize existing resources, it is hoped that the world of education can further maximize the potential of its students through efficient, creative, and innovative learning methods.